Do chlorides qualify as accelerators for the cement of deepwater oil wells at low temperature?. (15th February 2017) - Wang, Chengwen; Chen, Xin; Wang, Ruihe
Highlights: Accelerating ability of chlorides follows the order of CaCl2  > LiCl > KCl. LiCl has the most excellent comprehensive performance. CaCl2 increases the adiabatic temperature most and causes "flash set". Cement containing 3% LiCl generates the strip-like and the spherical particle CSH gels. Abstract: In this paper, the acceleration performances and mechanisms of chlorides (CaCl2, LiCl and KCl) on oil well cement at low temperatures were studied. The results indicated that their accelerating ability follows the order of CaCl2  > LiCl > KCl. CaCl2 has some unfavorable effects on the performance of cement, such as increasing the adiabatic temperature, causing bad rheology and thixotropy of cement slurry, and thickening the slurry, which may cause a "flash set". LiCl can significantly enhance the compressive strength development of oil well cement stone at low temperatures like CaCl2, but do not have the disadvantages of CaCl2 . Besides, LiCl can effectively shorten the static gel strength from 48 Pa to 240 Pa and also have much smaller adiabatic temperature. Based on the micro-test analyses, it was found that LiCl can accelerate the hydration rate of oil well cement under low temperatures. The hydration products of cement slurry include the ettringite (AFt), strip-shaped CSH gel (250–350 nm) and strip-shaped CSH gel (50–70 nm). The small spherical CSH gel fills in the pores of strip-shaped CSH gel to form a dense spatial structure. On contrast, the CSH gel forms a network structure in the cement containing CaCl2 or KCl. CaCl2 also inhibits the generation of AFt.